Pengaruh Pajak, Exchange Rate Dan Kepemilikan Asing Terhadap Transfer Pricing - Wendy Salim Saputra; Caroline Angela; Cindy Agustin (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2020)
The purpose of this study was to determine the factors that influence the transfer pricing policy of the company. This study uses secondary data, namely financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2016 to 2018. The sample selection technique that will be used is using a purposive sampling method. The analysis technique used is multiple linear regression analysis. Taxes and exchange rates have no effect on transfer pricing while foreign ownership has a positive effect on transfer pricing. The company has various reasons for conducting transfer pricing so investors need to carefully analyze company policies so as not to get caught up in the reports presented by the company's management. In addition, the government as a regulator must also review various policies related to transfer pricing to minimize the occurrence of adverse transfer pricing actions. The limited manufacturing companies with a multinational level so that the samples obtained are still limited and the lack of information about the transfer pricing carried out by the company.